Application of algal biomass for enhanced acclimatization of orchids - Virág, Emese; Molnár, Zoltán; Ördög, Vince (Acta Biologica Szegediensis, 2011)
Algae produce plant growth regulators (PGRs), similar to higher plants. To study this feature, freeze-dried and ultrasonicated algal biomass was applied to support the development of certain orchids. An in vitro and an ex vitro experiment were carried out. In case of Phalaenopsis and Paphiopedilum, the nutrition medium was supplemented with the biomass of five algal strains at a concentration of 0.5 gL-1 in the in vitro experiment. This treatment enhanced the development of plants, but different strains depending on orchid species proved to be efficient. In Oncidium cultures different concentrations of MACC-612 were applied as a supplementation of nutrition media. Results showed, that higher concentrations (0.5 – 1 gL-1) evolved a salutary effect on the plant growth. In the ex vitro experiment orchids were grown on algal free media under sterile conditions. After that they were potted into the greenhouse and treated eleven times with different concentrations of algal suspension. After three months of acclimatization the lower concentrations (0.1 – 0.2 gL-1) of algal biomass applied in the cultures of Phalaenopsis, Paphiopedilum and Oncidium exerted a positive effect.